From Langgars to Madrasas: The Arab School Movement in Central-Southern Java, 1900–1950 - Ahmad Athoillah (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
The social-religious gap between the Langgar and pesantren education systems within the context of colonial education policy was one of the reasons for the emergence of the movement to establish Arabic schools in south-Central Java during the first half of the 20th century. This research aims to explain the social-religious movement of organizational and non-organizational actors fighting for the right to religious education for children of primary school age in several districts and subdistrict centers in south-Central Java. Using the historical method, this research collected data from archives and scholarly works on religious social movements, focusing on movement actors, mobilization, and religious social change. The results indicated that the Arab school movement actors in South-Central Java were religious social organization activists, religious officials, and educational figures who mobilized their internal networks to construct new meanings and identities as religious social change unfolded. The study concludes that the Arab school movement has succeeded in transforming the new collective religious social identity in South-Central Java by enabling Arab school alumni to become an autonomous group alongside alumni of Islamic boarding schools and graduates of hegemonic colonial schools. They succeeded in becoming village officials who guided the religious-social community in south-Central Jva to follow the flow of religion.